Sublethal Effects of Acoustic Dummy Tag Implantation and External Tags in Silver Carp. (17th October 2022) - Coulter, Alison A.; Coulter, David P.; Lark, Ellen; Fritts, Mark W.; Davis, Cameron; Glover, David; Goforth, Reuben
Abstract: Telemetry data collected via internally implanted transmitters are commonly used to monitor and manage invasive Silver Carp Hypophthalmichthys molitrix . However, the extent to which posttagging effects may influence fish behavior is generally overlooked in telemetry studies. Moreover, internal telemetry tags are often combined with an external tag that can also affect fish growth and survival. This study used two pond experiments to (1) evaluate the temporal effects of internal telemetry tags, external jaw tags, and the combination of the two tags on survival, relative weight, growth, and inflammation; and (2) compare the effects of two external tag types (jaw and loop tags) on Silver Carp. Response variables were evaluated at three time points: 1, 2, and 5 months posttagging. Growth and relative weight were lower in fish that received jaw tags than in the control group or in fish that received internal tags only; however, growth was different at 1 month posttagging but not at 2 months posttagging, indicating potential compensatory growth. Shedding rate of internal tags was 14%; after 5 months, inflammation was absent and tags were encapsulated in tissue. Survival was similar between loop‐ and jaw‐tagged fish (73%), although growth was lower in jaw‐tagged fish. Results indicate that survival effects and sublethal effects of telemetry tagging may be temporary, and researchers should examine detection data from within 1–2 months of tagging for possible postsurgery effects. Jaw tags reduced growth, and loop tags had reduced retention; therefore, further evaluation of alternative external tags is needed to optimize telemetry studies focused on Silver Carp. Additionally, researchers need to carefully evaluate which external tag to use to facilitate the returns of more expensive acoustic telemetry tags and whether external tags are necessary in a particular case.